1991
DOI: 10.1128/jcm.29.2.407-409.1991
|View full text |Cite
|
Sign up to set email alerts
|

Rapid, on-site diagnosis of chlamydial urethritis in men by detection of antigens in urethral swabs and urine

Abstract: First-void urine (FVU) sediments of 240 men were tested for Chlamydia trachomatis antigens by two enzyme immunoassays, TestPack Chlamydia (15 min) and Chlamydiazyme (3.5 h), and the results were compared with urethral swab culture results. The sensitivity and specificity on FVU sediment for TestPack Chlamydia were 76.2% (32 of 42 specimens) and 95.5% (189 of 198 specimens) versus 81.0% (34 of 42 specimens) and 96.5% (191 of 198 specimens) for Chlamydiazyme, respectively. Rapid, on-site detection of chlamydial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 8 publications
0
19
0
Order By: Relevance
“…A urethral swab was taken from each patient and examined for C . trachomatis and urethral leukocytes; men with more than 4 leukocytes/hpf, which could indicate urethritis (Bowie, 1978;Swartz et al, 1978), were also excluded from the study. VB,, VB2, post-prostatic massage urine specimens (VB,), and expressed prostatic secretions (EPS) were cultured quantitatively for U. urealyticum and for common bacteria.…”
Section: Methodsmentioning
confidence: 99%
“…A urethral swab was taken from each patient and examined for C . trachomatis and urethral leukocytes; men with more than 4 leukocytes/hpf, which could indicate urethritis (Bowie, 1978;Swartz et al, 1978), were also excluded from the study. VB,, VB2, post-prostatic massage urine specimens (VB,), and expressed prostatic secretions (EPS) were cultured quantitatively for U. urealyticum and for common bacteria.…”
Section: Methodsmentioning
confidence: 99%
“…The idea of using self-taken, noninvasive specimens such as urine, especially when combined with antigen detection tests such as the enzyme immunoassay (EIA), has resulted in a move away from routine use of urethral swabs. Comparative studies have shown that although urethral swabs gave higher rates of detection than first void urine for both sensitivity and specificity (81.0% vs 76.2% and 99.0% vs 95.5%, respectively) when an EIA test was used (Sellors et al, 1991), the difference between the specimens was reduced when a nucleic acid amplification test (NAAT) was used (96.2% vs 92.5% and 100% vs 100%, respectively) (Carroll et al, 1998). A recent systematic review has confirmed the latter finding (Cook et al, 2005).…”
Section: Which Specimen?mentioning
confidence: 99%
“…The only other evaluation of the Testpack Chlamydia assay with FVU specimens from men was published by Sellors et al (17). They compared the results of the test with FVU specimens to the results of urethral swab cultures and showed that the Testpack Chlamydia assay was 76.2% sensitive and 95.5% specific, whereas the Chlamydiazyme assay was 81.0% sensitive and 96.5% specific.…”
Section: Discussionmentioning
confidence: 99%